Potret Kepemimpinan dalam Islam: Analisis Kepemimpinan Ala An-Nahdliyin (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2023)
This research is based on the author's concern in seeing the problematic condition of leadership today. Currently there are many Muslim leaders who use Islam as their distinctive identity, but they become political adventurers who are not moral. Not a few leaders appear in the midst of society with the slogan of fighting for Islam and Muslims, but act corruptly and embarrass Muslims in the midst of the public, with this research it is hoped that it can formulate the ideal character of a leader. This research method is library research with primary sources in the form of the book al-Ahkam as-Sulthaniyah by Abu Hasan Ali ibn Muhammad al-Mawardi and secondary references in the form of books, scientific papers, articles and journals related to an-Nahdliyin style leaders. The results of the study stated that the Islamic leader Ala An-Nahdiyin was institutionalized to replace the role of prophethood in order to protect religion and regulate world life. Islamic leadership of Ala an-Nahdiyin should not rely on packaging alone, if in practice it has implemented the Islamic spirits then it can be said to be a form of Islamic leadership.